Examining the Mediating Role of Organizational Culture in the Relationship Between Knowledge-Oriented Leadership Style and Innovative Performance in the General Directorate of Education in Mazandaran Province - Esmaeili, Neda; Faramarzi , Narjes; Talebzadeh Khoshrody, Fatemeh; Rezaei Rad, Mojtaba (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The primary objective of this study is to investigate the role of knowledge-oriented leadership on innovative performance with the mediating role of organizational culture in the General Directorate of Education in Mazandaran Province. Methodology: Given the nature of the study, which seeks to examine the relationship between the research variables, the present research is of a survey type. The statistical population of this study includes the employees of the General Directorate of Education in Mazandaran Province, totaling 140 individuals according to the inquiry from the personnel office, who were employed in 2021. The sample size was determined to be 103 individuals based on the Krejcie and Morgan table and selected through random sampling. The data collection tools used in this study were standardized questionnaires: the knowledge-oriented leadership questionnaire by Donate and de Pablo (2015), Hofstede’s (1984) organizational culture questionnaire, and Eskandarzadeh’s (2014) innovative performance questionnaire, which were distributed among the employees. Data analysis was performed using PLS2 and included the T-statistic and the path coefficient between two variables. Findings: The results showed that there is no significant relationship between knowledge-oriented leadership and organizational culture. Additionally, there is no significant relationship between organizational culture and innovative performance. Furthermore, organizational culture does not have a mediating role in the relationship between knowledge-oriented leadership and innovative performance in the General Directorate of Education in Mazandaran Province. Conclusion: Overall, it can be stated that the mediating role of organizational culture in the relationship between knowledge-oriented leadership style and innovative performance was not confirmed.